128k views
2 votes
Solve -2(2x+5) -3(x-1)

1 Answer

4 votes

Hello!

The answer is:


-2(2x+5)-3(x-1)=-7x-7\\

Why?

To solve the problem, we need to perform the operations and then, add like terms.

We need to apply the distributive property, which is defined by the following way:


a(b+c)=ab+ac

Also, we need to remember how to add like terms. Like terms are terms that share the same exponent and the same variable, for example:


3x+5x+x^(2)=8x+x^(2)

We were able to add only the first two terms since they are like terms, both are sharing the same exponent and the same variable.

So, we are given the expression:


-2(2x+5)-3(x-1)

Then, solving we have:


-2(2x+5)-3(x-1)=-4x-10-(3x-3)\\\\-4x-10-(3x-3)=-4x-10-3x+3\\\\-4x-10-3x+3=-4x-3x-10+3\\\\-4x-3x-10+3=-7x-7

Hence, we have that the answer is:


-2(2x+5)-3(x-1)=-7x-7\\

Have a nice day!

User Maddy D
by
5.5k points